COMUNICACIÓN GUBERNAMENTAL Y LA CONSTRUCCIÓN DE LA CONFIANZA EN LOS GOBIERNOS DE GUILLERMO LASSO Y DANIEL NOBOA¨ - CABANILLA LEÓN ANA GABRIELA (2024)
The purpose of this study, which has as its theme: Governmental communication and the building of trust in the governments of Guillermo Lasso and Daniel Noboa, is to evaluate how well the communication tactics of these two Ecuadorian presidents worked. The ability of any country to remain stable and move forward depends to a great extend on the faith that citizen have in their leaders. This paper seeks to explain how communication strategies can influence civil society opinion and support. In addition, it seeks to understand the strategies employed to foster openness and citizen participation through an in-depth examination of communication tactics, along with the influence these tactics have had on establishing public trust during their individual terms in office. The research is focused on identifying the different ways of communication employed by both governments, since in this way we will achieve our general objetive. Also, the perception of the Ecuadorian population on the transparency of information promoved by Lasso and Noboa will be analyzed. To conclude, we will evaluate the effectiveness of these strategies in building public trust, which will allow us to offer a critical and comparative perspective on the communication management of both leaders. Thes integrated approach aims to provide an in-depth understanding af how communication can be a crucial instrument for building the trust and legitimacy of an administration in the ayes of its people.